2022
DOI: 10.18844/wjet.v14i4.7620
|View full text |Cite
|
Sign up to set email alerts
|

Designing multimedia development for English language learning: Resources of effective instructional process

Abstract: Innovation in learning media development to facilitate students in supporting optimal learning outcomes is essential. This study aims to design mobile learning multimedia development production related to the mastery of English as a communication tool at the secondary level. It applies the following (4D) procedure: 1) define, which includes theoretical and need analysis; 2) design, which contains an identification of core competencies and basic competencies, selection and collection of materials, making flowch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It aims to design mobile learning multimedia development production related to mastery of English as a communication tool at the secondary level. It has been concluded that the pedagogical competence prepared in language teaching is very important (Harangus, 2021;Sukirman & Setiawan, 2022). It explores its role in developing and improving language skills by reading, writing, speaking and listening.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…It aims to design mobile learning multimedia development production related to mastery of English as a communication tool at the secondary level. It has been concluded that the pedagogical competence prepared in language teaching is very important (Harangus, 2021;Sukirman & Setiawan, 2022). It explores its role in developing and improving language skills by reading, writing, speaking and listening.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…While digital media is a type of media that requires computer equipment to use. Various media classified as traditional media are: books, posters, realia, and models (Gawrisch et al, 2019;Sukirman & Setiawan, 2022). The rapid advancement of digital technology, for example, has had little impact on the usage of printed teaching materials as a learning resource.…”
Section: Digital Media Conceptmentioning
confidence: 99%